Fire - Rosotti, Hazel (Oxford Univ. Press, 1993)
Is fire an element? How can we know when a pot was fired? When was fire insurance started? Why can custard powder explode? How can we reduce smog? How do we extinguish a blazing oil-well? Why is fire so prominent in religion and poetry? How does it spread through a building, and through a forest? This books aims to tease out the common thread which runs through the immensely varied phenomena which we call fire. Adopting a lively approach, and with the imaginative use of illustrations, the author explores five broad themes: Fire, the phenomenon; Fire for comfort; Fire for use; Fire as a hazard; and Fire for contemplation. The non-mathematical approach will appeal to the general reader, while experts in one field of combustion will find much to interest them in the many areas which border on their own.